The Seasonality of Respiratory Viruses in Patients with Chronic Rhinosinusitis. Issue 1 (January 2015) - Lima, Jesse T.; Paula, Flavia E.; Proença-Modena, José L.; Demarco, Ricardo C.; Buzatto, Guilherme P.; Saturno, Tamara H.; Delcaro, Luana S.; Tamashiro, Edwin; Valera, Fabiana C. P.; Arruda, Eurico; Anselmo-Lima, Wilma T.
Background: Chronic rhinosinusitis (CRS) is a common illness, yet little is known about its pathogenesis, including the role played by respiratory viruses. Methods: A transversal prospective study was conducted to analyze the seasonality of CRS using real-time polymerase chain reaction to detect respiratory virus genomes in secretions and tissue samples from patients with CRS with and without nasal polyps. Results: The frequency of viral detection was 41% (31/75). The respiratory virus most frequently detected was human rhinovirus, found in 18 patients (24%), followed by human metapneumovirus, human enterovirus, human respiratory sincicial virus, human adenovirus, human bocavirus, human coronavirus, and human influenza virus, detected in 12 (16%), five (6.6%), four (5.3%), four (5.3%), two (2.6%), two (2.6%), and one (1.3%) patient(s), respectively. Although none of the patients presented symptoms when the samples were collected, there was a peak in detection of the most prevalent virus in the autumn and winter seasons of both years, similar to the pattern that occurs in acute conditions. Conclusions: The pattern of respiratory virus seasonality found in nasal mucosa, polyps, and paranasal sinus samples in patients with CRS reinforces the possibility of asymptomatic respiratory viral infections.